In Vitro and In Vivo Toxicity of Garcinia or Hydroxycitric Acid: A Review. (9th August 2012) - Chuah, Li Oon; Yeap, Swee Keong; Ho, Wan Yong; Beh, Boon Kee; Alitheen, Noorjahan Banu
Abstract : Obesity is one of the pandemic chronic diseases commonly associated with health disorders such as heart attack, high blood pressure, diabetes or even cancer. Among the current natural products for obesity and weight control, Garcinia or more specifically hydroxycitric acid (HCA) extracted from Garcinia has been widely used. The evaluation of the potential toxicity of weight control supplement is of the utmost importance as it requires long term continuous consumption in order to maintain its effects. Majority of reports demonstrated the efficacy of Garcinia /HCA without any toxicity found. However, a few clinical toxicity reports on weight-loss diet supplements of which some were combinations that included Garcinia /HCA as an active ingredient showed potential toxicity towards spermatogenesis. Nonetheless, it cannot be concluded that Garcinia /HCA is unsafe. Those products which have been reported to possess adverse effects are either polyherbal or multi-component in nature. To date, there is no case study or report showing the direct adverse effect of HCA. The structure, mechanism of action, long history of the use of Garcinia /HCA and comprehensive scientific evidence had shown "no observed adverse effect level (NOAEL)" at levels up to 2800 mg/day, suggesting its safety for use.